The Relationship between Propagation Time and Sound Velocity Profile for Positioning Seafloor Reference Points. Issue 2 (4th March 2019) - Sun, Wenzhou; Yin, Xiaodong; Zeng, Anmin
Abstract: This paper focuses on the relationship between the propagation time and the integral of the sound velocity profile (SVP) with respect to depth (SVP area for short) for positioning seafloor reference points. We proved a linear relationship between the propagation time and the SVP area and defined its mathematical expression (ST law). We showed in three simulations of possible variations in SVPs (random errors, internal waves, or a combination of both) that this ST law is verified. Using this new law in a simulated experiment, the ranging residuals due to sound velocity change through time are significantly improved. With this method, monitoring the SVP while acquiring travel times to a submerged transponder can significantly reduce the positioning errors of the transponder.